Implementation of fully electric propulsion and variable speed drive to reduce ships emissions for sustainable maritime technology - Rahman, Abdul; Antariksa, Antariksa; Semedi, Bambang; Wahyudi, Slamet (Edelweiss Applied Science and Technology, 2025)
Implementing fully electric propulsion systems and variable speed drives (VSD) in warships to enhance electric load management and reduce exhaust emissions. The maritime industry is facing increasing pressure to adopt sustainable technologies to mitigate environmental impacts, especially in reducing greenhouse gas emissions from ships. Fully electric propulsion systems, combined with VSD technology, offer a promising solution by optimizing energy efficiency, minimizing fuel consumption, and decreasing operational emissions. The study presents a detailed analysis of the integrated electric propulsion system, highlighting its ability to provide dynamic power distribution based on the ship’s operational needs. By utilizing VSDs, the system can adjust the speed of electric motors in response to varying load demands, thereby reducing unnecessary energy consumption. This approach significantly contributes to lowering the ship’s overall carbon footprint. A case study on an LPD ship was conducted to evaluate the practical effectiveness of the proposed system. The results indicate a substantial reduction in fuel consumption and exhaust emissions, demonstrating the system’s potential to align with international maritime environmental regulations, such as the IMO’s emission standards. Additionally, the study explores the operational benefits, including improved power stability and enhanced performance during different operational modes, such as docking, cruising, and maneuvering. This research contributes to the growing knowledge of sustainable ship design and propulsion technologies and offers practical insights for ship operators and engineers aiming to transition to more eco-friendly maritime practices.